Pheromones and animal behavior : - Wyatt, Tristram D. (Cambridge University Press, 2014)
Pheromones and other kinds of chemical communication underlie the behavior of all animals. Building on the strengths of the first edition, widely recognized as the leading text in the subject, this is a comprehensive overview of how pheromones work